EDUKASI MARKETING BANK SYARÎ’AH - Wadhan Wadhan (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2011)
Abstract: Marketing is a significant aspect to increase consumer trust. Hence, it is essential to educate the consumer with the lesson of the importance of syarî’ah products concerning the marketing aspects. In fact, many banks serves the customer with syariah service in Indonesia. The basic concept of spiritual marketing is the managements of creation, taste, heart and work (the implementation). Those concepts are under the guidence of faith integrity, obidience, and loyality to Allâh swt. The key of ethics and moral of business is truly placed on the doers. A Muslim busines manager must hold tightly the ethic and moral of business that cope –khusn al-huluq, trusty, dan tolerant. There are three marketing strategies of syariah banking; marker driven strategic, viral marketing way, and fish net strategy. Element of mega marketing that had been intruduced by Rasûlullâh since the fifteenth century, and now can be adopted to any kinds of businesses including syariah banking. Key Words: Marketing, Marketer, dan Mega Marketing